Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content:1. Rashid Zaid Al-Kilani (1905 - 1965 A.D) his life and poetryDr. Anwar Mohammad Hamad Al- Tawarah2. Music of SoundsCo-Prof. Ibrahim Abdalla Ibrahim , Co-Prof. Jamal Edin Ibrahim Abdalrahman Ahmed , Asst-Prof. Fatima Omer Alsayer Zahid , Co-Prof. Mohammed Abdalla Mohammed Fadlala3. The directive principles for the phenomenon of the grammatical interpolation according to Abu Hayan Al Andalusi in Al Bahr Al MuhitDr. Wassim Zakaria Al-Kaakati4. Minor Sentence Link in The Noble Qur’anCo-Prof. Alwaleed Hassan Ali Mosalam5. The stylistic shift in diwan/poetical work (Al-Kademon Al-Kodor)Mrs. Nouf Yahya Mehzri, Prof. Hanan Abdullah Al-Ghamdi6. Indications of the strength and weakness of the linguistic sounds in the rain song poem by Al-Sayyab: Analytical descriptive studyMrs. Narmeen Ghalib Ahmed7. The manifestations of the implicit reader in the story of the tilted palm tree by Muhammad Ali TahaMrs. Samah Yousef Hasan Abu Ryash
Keywords: Journal of Arabic Language and Literature